Manajemen Pengelolaan Kelas Daring Pada Masa Pandemi - Dwi Novita Sari; Wardi (Journal of Social Sustainability Management, 2021)
The Covid-19 pandemic has prompted various changes that have forced many people from various statuses and professions to adapt. The realm ofeducation has also undergone many adjustments, starting from the learning process carried out in a distance, especially for areas outside the green zone. Schools unpreparedness to implement distance schools through the online system raises many obstacles. One of them is because the teachers themselves are still unfamiliar with the use of tools in online learning systems. Giving material in written or video form requires students to learn more independently. This is certainly not easy for students. Often they get bored and this affects their interest in learning. It takes online classroom management that is more than just giving attached assignments or videos. This study provides an overview of how good classroom management is to support the implementation of online teaching and learning activities. By using the descriptive analytical research method, it was found that online learning media act as a learning class. Teachers need to master online learning media to create creative learning in school from home activities. In the end, it was found that classroom management during the pandemic was more focused on non-physical matters, including: Interaction of students both with teachers and between students, learning environment, emotional and intellectual side. With this research, it is hoped that educators can consider various things in arranging online learning activities. Pandemi covid-19 mendorong terjadinya berbagai perubahan yang memaksa banyak kalangan dari berbagai status dan profesi harus beradaptasi. Ranah pendidikanpun mengalami banyak penyesuaian, mulai dari proses pembelajaran yang dilakukan jarak jauh, terutama untuk wilayah diluar zona hijau. Ketidaksiapan sekolah untuk melaksanakan sekolah jarak jauh lewat system daring memunculkan banyak kendala. Salah satu diantaranya disebabkan karena pihak guru sendiri masih awam mengenai penggunaan tools dalam system pembelajaran daring. Pemberian materi dalam bentuk tertulis maupun video, menuntut siswa untuk belajar lebih mandiri. Hal ini tentu tidak mudah bagi siswa. Tak jarang mereka bosan dan hal ini mempengaruhi minat belajarnya. Dibutuhkan pengelolaan kelas daring yang lebih dari sekedar pemberian tugas terlampir ataupun video. Penelitian ini memberikan gambaran bagaimana pengelolaan kelas yang baik untuk mendukung pelaksanaan kegiatan belajar mengajar via daring. Dengan menggunakan metode penelitian deskriptif analitif, didapati bahwa media pembelajaran daring berperan sebagai kelas belajar. Guru perlu menguasai media belajar daring untuk menciptakan pembelajaran yang kreatif dalam kegiatan school from home. Pada akhirnya didapati pengelolaan kelas dimasa pandemic lebih memfokuskan hal-hal yang bersifat nonfisik, meliputi: Interaksi peserta didik baik degan guru maupun antar siswa, lingkungan belajar, sisi emosional dan intelektual. Dengan adanya penelitian ini diharapkan para pendidik dapat mempertimbangkan berbagai hal dalam menyusun kegiatan pembelajaran via daring.